(untitled) - Gunnit S Khurana (Corte madera, 1996)
Getting started; Dissecting a job listing system; Building a database with microsoft access; Building microsoft access queries; Designing advanced queries; Elements of the world wide web; Creating HTML forms; Windows common gateway interface...
Keywords: database design,microsoft access,microsoft visual basic